SAE Technical Paper Series 2005
DOI: 10.4271/2005-01-2688
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Restrictive Clothing on Balance and Gait using Motion Capture and Stability Analysis

Abstract: The effect of restrictive clothing on functional reach and on balance and gait during obstacle crossing of five normal subjects is presented in this work using motion capture and stability analyses. The study has shown that restrictive clothing has considerably reduced participants' functional reach. It also forced the participants to change their motion strategy when they cross-higher obstacles. When crossing higher obstacles, the participants averted their stance foot, abducted their arms, flexed their torso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In another study by Egan et al [6], it was revealed that clothing properties such as weight can be another factor which have effects on balance and gait of people. Furthermore, Rahmatalla et al [14] concluded that restrictive clothing can impose constraints on the relative joint angle limits of the walking subject and therefore affect their gait pattern. In the study carried out by Phillips et al [15] for gait recognition using the silhouette-based approach, the recognition rate dropped sharply to 3% for the following combined covariate factors: time, footwear and clothing.…”
Section: The Clothing Effectsmentioning
confidence: 99%
“…In another study by Egan et al [6], it was revealed that clothing properties such as weight can be another factor which have effects on balance and gait of people. Furthermore, Rahmatalla et al [14] concluded that restrictive clothing can impose constraints on the relative joint angle limits of the walking subject and therefore affect their gait pattern. In the study carried out by Phillips et al [15] for gait recognition using the silhouette-based approach, the recognition rate dropped sharply to 3% for the following combined covariate factors: time, footwear and clothing.…”
Section: The Clothing Effectsmentioning
confidence: 99%
“…The optical sensors approach is both effective and efficient for collecting objective data for 3D motion analysis. Today, optical systems have many applications in biomechanical studies [12][13][14][15][16]. These systems have been shown to be accurate, repeatable, and consistent [17], and, as an additional benefit, there is no pain or risk involved in using such systems.…”
Section: Motion Capture Processmentioning
confidence: 99%
“…Alternatively, if the clothing does not permit heat to be conducted or convected away from the body, the wearer can suffer heat-induced fatigue or stroke. A recent study by Rahmatalla et al (2006) found that the stability of human motion can be significantly affected by clothing restrictions, which eventually causes wearers to change their strategies for accomplishing physical tasks.…”
Section: Introductionmentioning
confidence: 99%